Prognostic Factors of IVF&ICSI Cycle Cancellation in Patients with Endometriosis-Related Infertility - Elif Kulahci Aslan; Kiper Aslan; Cihan Cakir; Isil Kasapoglu; Berrin Avci; Baris Ata; Gurkan Uncu (Gynecology Obstetrics & Reproductive Medicine)
Objective: To elucidate the prognostic factors for intracytoplasmic sperm injection cycle cancellation in patients with endometriosis-related infertility.